Penerapan Prinsip Kerja Sama Pada Tuturan Yang Mengandung Alih Kode Dalam Komunikasi Karyawan Biro Perjalanan Wisata Di Kabupaten Badung, Bali - Permana, Deco Widi; Dewi, Ni Made Andry Anita (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 1 (2022)DO - 10.24843/JS.2022.v04.i01.p01, 2022)
This research determine the application of the principles of cooperation behind the communication of Travel Agents employees in Badung. This research used theory of cooperation principles by Grice and code switching theory by Wardhaugh. The methods and techniques used in data collection are observation methods and tapping techniques. For data analysis are descriptive qualitative methods and descriptive techniques. The data presentation stage used an informal method. The results obtained in this research are 5 pieces of data including the type of situational code switching. In this research was found that 1 data on the application of the maxim of quantity, 1 data as a form of application of the maxim of quality, 1 data on the application of the maxim of relevance, 1 data on the application of the maxim of relevance, and 1 data on the application of the maxim of implementation.